2013
DOI: 10.1111/hae.12182
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in haemophilia patients: effect on bleeding frequency, clotting factor concentrate usage, and haemostatic and fibrinolytic parameters

Abstract: The prevalence of obesity in patients with haemophilia (PWH) is increasing. We investigated the effect of obesity on bleeding frequency and clotting factor concentrate (CFC) usage in PWH and assessed whether prothrombotic changes observed in obesity differ between controls and PWH. Number of bleeds and CFC usage were compared between obese (N = 51) and non-obese (N = 46) haemophilia A patients. Markers of haemostasis and fibrinolysis were compared between PWH, and gender-, age- and body mass index (BMI)-matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…The mechanisms of obesity‐associated arthropathy are yet to be elucidated. Obesity had no effect on bleeding frequency, but was associated with a 1.4 fold increase in the use of clotting factor concentrates in a study comparing 51 obese and 46 non‐obese patients with haemophilia A .…”
Section: Obesity and Its Impact On Complications And Dosingmentioning
confidence: 96%
“…The mechanisms of obesity‐associated arthropathy are yet to be elucidated. Obesity had no effect on bleeding frequency, but was associated with a 1.4 fold increase in the use of clotting factor concentrates in a study comparing 51 obese and 46 non‐obese patients with haemophilia A .…”
Section: Obesity and Its Impact On Complications And Dosingmentioning
confidence: 96%
“…68 Some studies have found ~65% of haemophilia patients to be Vitamin D deficient; low vitamin D levels have a strong association with osteoporosis in haemophilia patients. 39,70,71 Therefore, optimizing vitamin D and achievement of an ideal BMI are crucial. 39,70,71 Therefore, optimizing vitamin D and achievement of an ideal BMI are crucial.…”
Section: General Considerations Throughout the Lifespanmentioning
confidence: 99%
“…This disease is classified as mild, moderate or severe, depending on the level of clotting factor VIII or IX in an individual's blood. 3,6,16,17 Limited data exist on the longitudinal impact of obesity and changes of weight, which are mostly derived from case reports. [2][3][4][5][6][7] In people with haemophilia (PwH), the prevalence of overweight (adults, 19%-59%; children, 15%-21%) and obesity (adults, 18%-36%; children, 17%-22%) is similar to that of the general US population.…”
Section: Introductionmentioning
confidence: 99%